Left Ventricular Mechanics Differ in Subtypes of Aortic Stenosis Following Transcatheter Aortic Valve Replacement - Wani, Adil; Harland, Daniel R.; Bajwa, Tanvir K.; Kroboth, Stacie; Ammar, Khawaja Afzal; Allaqaband, Suhail Q.; Duval, Sue; Khandheria, Bijoy K.; Tajik, A. Jamil; Jain, Renuka (Frontiers in Cardiovascular Medicine, 2022)
Background Left ventricular (LV) mechanics are impaired in patients with severe aortic stenosis (AS). We hypothesized that there would be differences in myocardial mechanics, measured by global longitudinal strain (GLS) recovery in patients with four subtypes of severe AS after transcatheter aortic valve replacement (TAVR), stratified based upon flow and gradient. Methods We retrospectively evaluated 204 patients with severe AS who underwent TAVR and were followed post-TAVR at our institution for clinical outcomes. Speckle-tracking transthoracic echocardiography was performed pre- and post-TAVR. Patients were classified as: (1) normal-flow and high-gradient, (2) normal-flow and high-gradient with reduced LV ejection fraction (LVEF), (3) classical low-flow and low-gradient, or (4) paradoxical low-flow and low-gradient. Results Both GLS (−13.9 ± 4.3 to −14.8 ± 4.3, P < 0.0001) and LVEF (55 ± 15 to 57 ± 14%, P = 0.0001) improved immediately post-TAVR. Patients with low-flow AS had similar improvements in LVEF (+2.6 ± 9%) and aortic valve mean gradient (−23.95 ± 8.34 mmHg) as patients with normal-flow AS. GLS was significantly improved in patients with normal-flow (−0.93 ± 3.10, P = 0.0004) compared to low-flow AS. Across all types of AS, improvement in GLS was associated with a survival benefit, with GLS recovery in alive patients (mean GLS improvement of −1.07 ± 3.10, P < 0.0001). Conclusions LV mechanics are abnormal in all patients with subtypes of severe AS and improve immediately post-TAVR. Recovery of GLS was associated with a survival benefit. Patients with both types of low-flow AS showed significantly improved, but still impaired, GLS post-TAVR, suggesting underlying myopathy that does not correct post-TAVR.